Peran Patroli Dialogis Roda Empat Satsabhara dalam Mencegah Tindak Pidana Curanmor di Wilayah Hukum Polres Sumedang - Rachman, Rafly Audifa (Indonesian Journal of Police Studies, 2020)
The rampant auto theft phenomena is causing disruption of kamtibmas. Police as a public servant should seeks to maintain the kamtibmas situation through dialogical four-wheeled vehicle patrol in preventing auto theft. Therefore, a study was conducted aimed to describe the auto theft phenomena and Satsabhara role under the dialogical four-wheeled patrol and indentify factors influencing the patrol. Theories used are Role, Routine-Activity, Communication, Crime Prevention, Management and Law System Theories. Subsequently, concepts used are dialogical patrol, four-wheeled patrol, auto theft, kamtibmas, Satsabhara, and Perkabaharkam No. 1 Year 2017. This research is conducted using qualitative approach and field research methods. Data is collected through interviewing, observing, and studying documents, and validated using triangulation of data. The results of the study found that cases of auto theft were the most common cases in Polres Sumedang. The role of dialogical four-wheeled patrol by Satsabhara in preventing auto theft was not optimal because shortages remain and there were still deficiencies in terms of Satsabhara officers' knowledge, and the ability to communicate. The inhibiting factors are organizational structure, human resources, budget, organizational policy factors, and Perkabaharkam No. 1 Year 2017, while supporting factors are facilities and infrastructures, other units of function support, cooperation with other agencies and community factors. Results of the study suggest evaluation on job description and bureaucracy, creation of a WhatsApp group, revision of Polres’ SOP on dialogical patrol, and maintain the auto theft-related materials carried by patrol officers and aiming propriate target are necessary to be done.